Chondrogenic differentiation of human adipose-derived stem cells in PLGA (poly(lactic-co-glycolic acid) scaffold - Rhie, Jong-Won; Cho, Hyun-Mi; Lee, Hee-Young; Han, Dong-Keun (ASBM7: ADVANCED BIOMATERIALS VII, 2007)
Human adipose tissue contain a population of pluripotent stein cells capable of differentiating along multiple mesenchymal cell lineages. The goal of this study was to examine the chondrogenic potential of adipose-derived stem (ADS) cells. ADS cells were isolated from human subcutaneous adipose tissue obtained by lipectomy and liposuction, and were expanded and grown in vitro with or without chondrogenic medium in micromass culture condition and 3D culture condition in PLGA(poly(lactic-co-glycolic acid)) scaffold. Human ADS cells of micromass culture condition and 3D culture condition in PLGA scaffolds, were differentiated with chondrogenic medium consisted of transforming growth factor-beta 1, insulin-transferrin-selenium, dexamethasone and ascorbate-2-phosphate. ADS cells abundantly symbesized cartilage matrix molecules including collagen type II, VI and link protein. ADS cells under high-density micromass Culture condition with chondrogenic medium formed well defined nodules within 48 hours of induction. On the 3rd week after chondrogenic differentiation of ADS cc Is under the micromass culture condition and 3D culture condition of PLGA scaffold, mRNA of tape II collagen, type VI collagen and link protein were expressed by reverse transcription polymerase chain reaction (RT-PCR). On the 3weeks, content of glycosaminoglycan in cells treited with chondrogenic medium was greater than that with non chondrogenic medium(control).Cn the 3rd week culture under the chondrogenic medium, hematoxylin & eosin (H & E) staining, alcian blue staining and type II collagen immunohistochemistry analysis confirmed the chondrogenic differentiation in micromass and 3D cultured specimen. These findings document the ability of ADS cells to produce characteristic cartilage matrix molecules, and provide the possibility of cartilage regeneration for cartilage substitution.